Bamboolike Carbon Microfibers Derived from Typha Orientalis Fibers for Supercapacitors and Capacitive Deionization. Issue 2 (24th January 2019) - Ma, Xiumei; Wang, Haining; Wu, Qinghao; Zhang, Jin; Liang, Dawei; Lu, Shanfu; Xiang, Yan
Abstract : The increasing demand for efficient energy storage and water desalination requires advanced porous carbon materials from biomasses due to their sustainability and renewability. The morphologies, microstructures, and properties of carbon materials were determined by the biomass precurors. Here, a novel bamboolike Typha orientalis fiber was selected as a precursor to prepare porous carbon material by carbonization and activation methods. The carbon material retains the bamboolike microfiber structure of the precursor and presents high specific surface area, well-balanced pore size distribution, and high conductivity and good hydrophilic property. It also displays a specific capacitance of 351 F g −1 at current density of 1.0 A g −1 as well as good stability over 10000 cycles for a supercapacitor as well as an outstanding salt adsorption capacity of 18.5 mg g −1 at voltage of 1.6 V and 81% retention after 55 cycles for capacitive deionization.